EFFECT OF MANNITOL INDUCED DROUGHT STRESS ON SEEDLING TRAITS AND PROTEIN PROFILE OF TWO WHEAT CULTIVARS - I. Ullah; N. Akhtar; N. Mehmood; I. A. Shah; M. Noor (Journal of Animal and Plant Sciences, 2014)
The experiment was carried out at the laboratory of Botany Department, Kohat University of Science and Technology, Kohat in December 2012. Two wheat cultivars (Janbaz and Atta Habib) were subjected to different mannitol levels (0, 125, 250 and 500 mM) under room temperature in petridishes. The objectives of the study were to investigate the effect of mannitol induced drought stress on seedling traits and protein profile of two wheat cultivars. Analyses of variance revealed significant differences for shoot and root length for mannitol levels as well as for interaction. Genotypes, however, showed significant variability for root length only. It was evident from the data that increased levels of mannitol decreased the shoot and root lengths linearly. The longest shoot (8.57 and 9.57 cm) and root (9.73 and 10.13 cm) were recorded from control treatments while the shortest shoot (3.03 and 2.67 cm) and roots (2.37 and 2.67 cm) were observed in 500 mM treatment for Janbaz and Atta Habib, respectively.96.1 and 88.6 % of variation in shoot length and 72.3 and 71.5 % variation in root length was due to the mannitol induced drought stress for Janbaz and Atta Habib, respectively. SDS-PAGE showed no band variation between genotypes as well as among mannitol levels.
Keywords: Drouht stress; mannitol; protein; root length; shoot length; SDS-PAGE